Evaluation of Unbalanced Load Impacts on Distribution Transformer Performances - Agung Pratama, Nurul; Rahmawati, Yuni (Frontier Energy System and Power Engineering, 2020)
Distribution transformers are useful as converters of electrical energy from higher to lower voltage levels. These parts also contribute to feeding energy to consumers. Technically, these transformers are required by many operational constraints. In general, the voltage drop should not exceed 5 % while the current imbalance should not exceed 10 %. In fact, these conditions are depended on the system performances. These works are addressed to explore these requirements based on operational power loading. Moreover, these studies are also focused on voltage and current profiles which are assessed to evaluate and maintain the quality of power transformers on the distribution system. Moreover, the evaluation is also concerned with unbalanced load impacts on transformer performances. Results show that voltage and current qualities are not meet the standards of the electricity system. The highest voltage condition is 237 volt while the unbalanced factor is over 2 % for each phase and the highest imbalance factor is covered in 7.73 %. The highest current imbalance factor reaches 41.9 % with various individual unbalance impacts.